Expression and significance of Toll-like receptor 5 in peripheral blood mononuclear cells of patients with rheumatoid arthritis - ZHANG Wenxin; XIONG Jinhe (Zhongguo linchuang yanjiu, 2024)
Objective To examine the expression levels of Toll-like receptor 5 (TLR5) on peripheral blood monocytes in patients with rheumatoid arthritis (RA), and to explore its clinical significance. Methods A total of 140 RA patients, along with 70 healthy controls (normal control group) received in Suining Central Hospital from January 2017 to August 2022 were selected. The RA patients were divided into high disease activity group (n=70) and moderate-to-low disease activity group (n=70) based on the disease activity score 28-erythrocyte sedimentation rate (DAS28-ESR). Flow cytometry was used to determine the positive rate of TLR5 on peripheral blood monocytes among three groups. The predictive value of TLR5 expression on monocytes surface for RA was analyzed using receiver operating characteristic (ROC) curves. Results The positive rates of TLR5 on the surface of monocytes in normal control group, moderate-to-low disease activity group and high disease activity group were (46.99±5.79)%, (50.80±5.96)% and (58.86±6.20)%, respectively, and there was a statistically significant difference among the three groups (F=71.550, P＜0.01). The area under the ROC curve for TLR5 in diagnosing RA was 0.79, with a cut-off value of 49.50%, sensitivity of 72.86%, and specificity of 73.57%. Conclusion The TLR5 expressed on peripheral blood monocytes is involved in the pathogenesis and maintenance of disease activity and has predictive value for RA.